PENINGKATAN KREATIVITAS DALAM PENGEMBANGAN KEWIRAUSAHAAN DI YAYASAN AL KAHFI KANTOR PERWAKILAN CIBEUYING KIDUL - Rici Solihin; Gatot Iwan Kurniawan; Dani Dagustani (Universitas PGRI Yogyakarta, 2021)
Education is the basic need of children in self development. However, the disparity in economic level between rich and poor families causes inequality in the quality of education that children received. Due to the limitations, poor families encourage their children to get additional care outside the family. Al Kahfi Foundation Cibeunying Kidul Representative Office is one of the social service institutions specifically designed as an alternative to take care of child from the marginalized. However, the current learning system is too rigid, monotonous and one-way thus cause the learning process does not encourage children's creative and critical thinking skills. This phenomenon is an opportunity for university to transfer knowledge and additional learning methods focus on forming creative solution thinking patterns for youth or students. By upgrading students' creative and critical thinking, we hope that various kinds of fresh ideas will be born as solutions to social problems through social entrepreneurship.